The influence of advertising appeals on viral advertising, brand awareness, and purchase intention: The moderator role of hedonic personality - Prajogo, Wisnu; Purwanto, Edi (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2020)
Viral advertising has become a trending topic nowadays. This study aims to examine the effect of advertising appeals on viral advertising, brand awareness, and purchase intentions with the hedonic personality playing as a moderating role. The use of hedonic personality itself to predict viral intentions, brand awareness, and purchase intentions have not been widely discussed by other researchers. This study can be classified as explanatory research with purposive sampling and partial least square as sampling techniques and data analysis. This study was designed to focus on individuals who can be classified as social media active users with a minimum age of 18 years old. The result shows that advertising appeals (humor and informative) have a positive and significant impact on viral intention and attitude toward advertisement. Thus, the higher viral intention and the positive attitude toward advertisement will increase the possibility of purchase and the level of brand awareness. While hedonic personality was significantly proved moderates the relationship between viral intentions and brand awareness in this study. The nature of respondents in this study who mainly are at high level of hedonic personality make the moderation role of hedonic personality has no significant impact on the relationship of viral intentions on purchase intentions. Therefore, the viral factor on hedonic consumers did not seem to correlate purchase intentions.